Iron-Palladium Decorated Carbon Nanotubes Achieve Radiosensitization via Reactive Oxygen Species Burst - Yang, Shengnan; Yang, Yiling; Yang, Yi; Zhao, Xiangya; Wang, Qian; Li, Bing; Dong, Ling; Tian, Rui; Bao, Zhirong (Frontiers in Bioengineering and Biotechnology, 2021)
Radiotherapy is recommended as a modality for cancer treatment in clinic. However, cancerous cells were resistant to therapeutic irradiation due to its DNA repair. In this work, single-walled carbon nanotubes with unique physical properties of hollow structures and high specific surface area were introduced as carrier for iron-palladium (FePd) to obtain iron-palladium decorated carbon nanotubes (FePd@CNTs). On one hand, FePd nanoparticles possess significant ability in radiosensitization as previously reported. On the other hand, carbon nanotubes offer higher efficiency in crossing biological barriers, inducing the accumulation and retention of FePd nanoparticles within tumor tissue. In order to verify the radiosensitization effect of FePd@CNTs, both in vitro and in vivo experiments were conducted. These experiments showed that the FePd@CNTs exhibited remarkably better radiosensitization effect and more obvious accumulation than FePd NPs, suggesting a potential of FePd@CNTs in radiosensitization.